(untitled) (Journal of Partial Differential Equations, 2020)
In his unremitting efforts to train mathematics talents, Professor Gu has greatly helped to bring up a large number of students, leading them onto their own way of mathematical research. Now many of them have become leaders or the backbone force in their respective departments and special areas. Because of his significant contributions to the educational cause of China, Professor Gu has been awarded many honors and titles such as the national advanced worker in 1956, a national labor model of the education in 1993, etc. Moreover, some university textbooks written by him with his group have received prizes for excellence from the state.